Clinical analysis of sarcopenia prevalence and its influencing factors in patients with Parkinson’s disease - Morimoto, Remi; Kitagawa, Kazuo; Todo, Kenichi; Iijima, Mutsumi (Frontiers in Aging Neuroscience, 2025)
BackgroundPatients with Parkinson’s disease (PD) have a high risk of sarcopenia. Herein, we evaluated the prevalence of sarcopenia and factors associated with it in ambulatory patients with PD.MethodsAmbulatory patients with PD up to Hoehn and Yahr stage III were included and evaluated based on age, sex, disease duration, levodopa equivalent daily dose, cognitive impairment, swallowing disturbance, history of falling, the Japanese version of the movement disorder society-sponsored revision of the unified PD rating scale (MDS-UPDRS) parts I–IV, quality of life (QoL), and blood test (total protein, albumin, and anemia). Cognitive impairment was assessed using the Japanese version of Mini-Mental State Examination and the Japanese version of the Montreal Cognitive Assessment, whereas swallowing disturbance was assessed using the Japanese version of the Swallowing Disturbance Questionnaire. QoL was assessed using the Parkinson’s Disease Questionnaire (PDQ-8). Sarcopenia was diagnosed based on handgrip strength, five-time chair stand test, and skeletal muscle mass.ResultsOverall, 97 patients with PD (55 males), with a mean age of 69.8 years and a mean disease duration of 7.3 years, were included. The prevalence of sarcopenia was 33.0%. There were significant differences between the sarcopenia and the non-sarcopenia groups in age, sex, swallowing disturbance, MDS-UPDRS part III total score, and the sub-items arising from a chair, postural stability, and global spontaneity of movement (p < 0.05). There was no association between the presence of sarcopenia and the PDQ-8 total and sub-item scores. The factors that contributed most to sarcopenia were being female, cognitive impairment, and swallowing disturbance.ConclusionIn clinical management, it is important to assess muscle strength and evaluate sarcopenia, particularly in patients with PD who have being female, cognitive impairment, or swallowing disturbance.